Biomarker P16 predicts progression risk of anal low-grade squamous intraepithelial lesions. (23rd October 2018) - Liu, Yuxin; Blakely, Morgan; Sigel, Keith; Thin, Tin Htwe; Hui, Pei; Donovan, Michael; Gaisa, Michael M.
Abstract : Objectives: The aim of this study was to determine whether biomarker P16 INK4a predicts progression risk for anal low-grade squamous intraepithelial lesions (LSILs). Design: A retrospective study. Methods: One hundred and nine HIV-infected and 18 HIV-uninfected patients with biopsy-proven anal LSIL at initial screening underwent surveillance high-resolution anoscopy and biopsy within 2 years of diagnosis. P16 immunohistochemistry was performed on index lesions and evaluated using a semi-quantitative scoring system. The association of predictors and lesional outcomes (progression, persistence or regression) was analysed using ordinal logistic regression models. A subset of p16-positive LSILs was tested for high-risk human papillomavirus (HR-HPV) DNA using real-time PCR. Results: Upon follow-up, 46 (36%) LSILs progressed to high-grade squamous intraepithelial lesion (HSIL), 50 (40%) persisted as LSIL and 31 (24%) regressed to benign mucosa (median 16 months, range 5–24 months). Age, sex, race, history of condylomata, CD4 + T-cell count and HIV plasma viral load were similar regardless of clinical outcome. P16 immunoreactivity of index lesion was classified as block-positive ( n  = 36), focal-positive ( n  = 49) or negative ( n  = 42). Sixty-four percent of block-positive lesions progressed, as opposed to 35% of focal-positive and 14% of negative lesions ( P  < 0.001). HR-HPV DNA was detected in 90% of p16 block-positive lesions vs. 55% of focal-positive lesions. In unadjusted analyses, positive p16, HIV and former smoker status were significantly associated with lesional persistence and progression. P16 remained the only significant predictor in an adjusted model. Conclusion: Biomarker p16 is the strongest predictor for anal LSIL-to-HSIL progression, outperforming other risk factors. To enhance the overall effectiveness of surveillance, we propose using p16 immunohistochemistry to help stratify patients at high vs. low risk of progression.